Managing stakeholders' influence on embracing business code of conduct and ethics in a local pharmaceutical company: Case of Kampala Pharmaceutical Industries (KPI). Issue 2 (6th June 2016) - Katamba, David; Marvin Nkiko, Cedric; Ademson, Consolate
Abstract : Purpose: This paper aims to avail a soft approach to embracing the process of creating a business code of conduct and ethics and make it work for a pharmaceutical company [player] which wants to remain relevant before stakeholders and society, amidst escalating inducements to go against the acceptable pharmaceutical behaviour. Design/methodology/approach: Data collection was guided by qualitative methodologies. A four stepwise process was followed: data collection at the case company – Kampala Pharmaceutical Industries (KPI), Uganda; validation of data collected at KPI; data collection from external stakeholders of KPI; and re-validation of KPI data based on data collected from external stakeholders. In all this, combination of semi-structured and informal interviews with CEOs, senior staff managers, non-participant observation of ethical related activities plus organizing a stakeholder engagement workshop on business code of conduct and ethics was achieved. This workshop helped document what ought to be an ideal design process to secure stakeholder buy-in of the code of business ethics. A local pharmaceutical company in Uganda, KPI was used, which, for continuous five years since its adoption of the business code of conduct and ethics, registered commercial viability without any record of unethical practices. Triangulation was used to ensure credibility and validity of the results. For data analysis, a three-stepwise process was followed, which helped develop a framework within which the collected data revealed themes which were later analyzed. For generalization of the findings, the "adaptive theory approach" was used. Findings: When poorly introduced in an organization, the business code of conduct and ethics can work against the company simply because it will be received with "intentional rebellion" from stakeholders, notably staff. However, when a soft stakeholder engagement and consultative approach is used and followed during the business code of ethics and conduct's design process, multiple stakeholders feel proud and are much willing to live by the promise spelt out in it. Cited notable benefits of living by the code include reputational enhancement, strategic competitiveness and increased possibilities of wining cross-border cooperation among like-minded pharmaceutical players. In the efforts to reap from the code of ethics, communication was observed as an indispensable activity. Refresher trainings to remind the stakeholders about the promises in the code are also needed as time passes by, otherwise they forget. Needless to say, rewarding those who live an exemplary life in embracing and living by the code was cited as key in sustaining the ethical agenda. Lastly, managing multiple stakeholders influences is a curvilinear fashion and involves back and forth consultations. Practical implications: The lessons learnt from KPI can be borrowed and used by both global pharmaceutical players and national/local players, especially those that face challenges living by the promise of their existing codes or those without business code of conduct and ethics. That is, both players can use the suggested process to help participants in their medicine supply chain to come up with working business codes of conduct, as well as guide the stakeholder consultative process which results in stakeholder buy-in. Originality/value: For many years, issues surrounding bioethics have dominated priorities of World Health Organization (WHO), UNESCO and many international and national development allies. However, there is an escalating violation of medical codes of conduct and ethics. Hence, this publication is a step toward the implementation of the principles and objectives of the UNESCO Universal Declaration on Bioethics and Human Rights which is currently challenged with a difficult question posed by life sciences – How far can we go given the dented medical relationship between ethics, medical science and freedom?